PEMASARAN DIGITAL UNTUK MENINGKATKAN DAYA SAING UMKM - Minah Aulia Habibah; Nesty Waruwu; Jenita Rizkiana; Muhammad Gandung (Abdi Jurnal Publikasi, 2026)
Digital marketing has become a strategic solution for Micro, Small, and Medium Enterprises (MSMEs) to improve competitiveness in the digital era. Many MSME actors still rely on conventional marketing methods, resulting in limited market reach and low sales growth. This community service program aims to improve MSME competitiveness through digital marketing training and mentoring. The methods used include socialization, training, hands-on practice, and evaluation of digital marketing implementation. The activities were carried out for MSME actors in the Pamulang area, focusing on the use of social media platforms, digital content creation, and simple online branding strategies. The results show an increase in participants’ understanding of digital marketing concepts, the ability to manage social media accounts, and improved product promotion quality. MSME actors also experienced increased engagement and broader market reach after applying digital marketing strategies. This program proves that digital marketing empowerment can enhance MSME competitiveness and sustainability. Continuous mentoring and digital literacy improvement are recommended to ensure long-term impact.